Garcinia atroviridis pastilles with anti-obesity potential - Mohd Ismail, Nurul Izzati; Mohd Ghazali, Jamilah; Fauzi, Basirah; Mohd Adnan, Raudah; Mohd Aripen, Nur Shahirah; Azeman, Nur Hasnatul Haniemah; Harun, Nur Hasanah; Mohamed, Norfatihah (Penerbit UTHM, 2020)
Garcinia atroviridis has been used as food seasoning since ancient times. Garcinia atroviridis was reported to contain anti-inflammatories, anti-fungal, antioxidant and anti-obesity properties. Nowadays, modern society has become more health conscious and was especially against obesity. Thus, it was important to search for a new solution to fight obesity using the more natural and toxin-free approaches.